Assessing the impact of a multidimensional approach and an 8-component bundle in reducing incidences of ventilator-associated pneumonia across 35 countries in Latin America, Asia, the Middle East, and Eastern Europe - Rosenthal, Victor Daniel (2024)
Background: Ventilator associated pneumonia (VAP) occurring in the intensive care unit (ICU) are common, costly, and potentially lethal. Methods: We implemented a multidimensional approach and an 8-component bundle in 374 ICUs across 35 low and middle-income countries (LMICs) from Latin-America, Asia, Eastern-Europe, and the Middle-East, to reduce VAP rates in ICUs. The VAP rate per 1000 mechanical ventilator (MV)-days was measured at baseline and during intervention at the 2nd month, 3rd month, 4–15 month, 16–27 month, and 28–39 month periods. Results: 174,987 patients, during 1,201,592 patient-days, used 463,592 MV-days. VAP per 1000 MV-days rates decreased from 28.46 at baseline to 17.58 at the 2nd month (RR = 0.61; 95% CI = 0.58–0.65; P < 0.001); 13.97 at the 3rd month (RR = 0.49; 95% CI = 0.46–0.52; P < 0.001); 14.44 at the 4–15 month (RR = 0.51; 95% CI = 0.48–0.53; P < 0.001); 11.40 at the 16–27 month (RR = 0.41; 95% CI = 0.38–0.42; P < 0.001), and to 9.68 at the 28–39 month (RR = 0.34; 95% CI = 0.32–0.36; P < 0.001). The multilevel Poisson regression model showed a continuous significant decrease in incidence rate ratios, reaching 0.39 (p < 0.0001) during the 28th to 39th months after implementation of the intervention. Conclusions: This intervention resulted in a significant VAP rate reduction by 66% that was maintained throughout the 39-month period.